BSG 2024 IBD guidelines protocol (standard operating procedures). Issue 1 (10th February 2023) - Darie, Ana-Maria; Sinopoulou, Vasiliki; Ajay, Verma; Bel Kok, Klaartje; Patel, Kamal V; Limdi, Jimmy; Arebi, Naila; Smith, Philip; Din, Shahida; Din, Said; Shale, Matthew; Subramanian, Sreedhar; et al.
Abstract : Introduction: In the past 5 years, there have been several advances in the management of inflammatory bowel disease (IBD). We aim for a new guideline to update the most recent guideline published in 2019. We present the prospective operating procedure and technical summary protocol in the manuscript. Methods: 'Grading of Recommendations Assessment, Development and Evaluation' (GRADE) will be followed in the development of the guideline, approach as laid out in the GRADE handbook, supported by the WHO. The guideline development group is formed by a variety of disciplines, across both primary and secondary care that took part in an online Delphi process and split into key areas. A final consensus list of thematic questions within a 'patient, intervention, comparison, outcome' format has been produced and agreed in the final phase of the Delphi process. There will be a detailed technical evidence review with source data including systematic reviews appraised with AMSATAR 2 tool (Assessment of multiple systematic reviews), randomised controlled trial data that will be judged for risk of bias with the Cochrane tool and observational studies for safety concerns assessed through the Robins-I tool. Based on the available evidence, some of the recommendations will be based on GRADE while others will be best practice statements. A full Delphi process will be used to make recommendations using online response systems. This set of procedures has been approved by the Clinical Services and Standards Committee, the British Society of Gastroenterology executive board and aligned with IBD UK standards.